Evaluation of nutrient composition and phenolic compound of pomegranate fruit waste as a novel feed for dairy cattle - Patil Saroja Popat; A. Bharathidhasan; R. Karunakaran; K. Vijayarani; P. Tensingh Gnanaraj (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The pomegranate (Punica granatum) belongs to the Punicaceae family and is a nutrient dense food source rich in phytochemical compounds.About 50 % of the total fruit weight corresponds to the peel, which is an important source of bio active compounds such as phenolics, flavonoids, ellagitannins (ETs) and proanthocyanidin compounds which can be used as an alternative feed source for dairy cattle. Hence, the present study was carried out to evaluate the nutrient composition and polyphenolic compound of pomegranate fruit waste (PFW) for dairy cattle. Six samples of PFW were collected from six different places in India and screened for their nutritional composition and polyphenolic compound. The results showed that pomegranate fruit waste contained 12.72 % DM, 4.80 % CP, 12.26 % CF, 3.43 % TA, 1.47 % EE, 65.3 % NFE, 28.21 % NDF, 23.30% ADF, 4.91 % Hemicellulose, 13.79 % Cellulose and 5.14 % Lignin. Polyphenolic compound of PFW were 2.57 % total phenolic compound, 2.43 % total tannin content, 0.13 % non-tannin phenolics, 1.75 % condensed tannin, 0.69 % hydrolysable tannin and 2.05% total flavonoid content. Thus, it is concluded that PFW is of high nutritive value which can be used for feeding to dairy cattle.